The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1089/jmf.2014.3214
|View full text |Cite
|
Sign up to set email alerts
|

Aged Red Garlic Extract Suppresses Nitric Oxide Production in Lipopolysaccharide-Treated RAW 264.7 Macrophages Through Inhibition of NF-κB

Abstract: Lipopolysaccharides (LPS) activate nuclear factor kappa B (NF-κB), a transcription factor that is involved in inflammatory response. The pathways that activate NF-κB can be modulated by phytochemicals derived from garlic. We recently demonstrated that aged red garlic extract (ARGE), a new formulation of garlic, decreases nitric oxide (NO) generation by upregulating of heme oxygenase-1 (HO-1) in RAW 264.7 cells activated by LPS. However, the effects of ARGE on LPS-induced NF-κB activation are unknown. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As oxidative stress is thought to be the mechanism through which dengue virus acts to trigger the pro-inflammatory immune response during infection, and garlic has previously been shown to suppress nitric oxide production [ 28 ], inhibit oxidative injury [ 29 ] and decrease reactive oxygen species (ROS) levels [ 32 ], we examined the anti-oxidant activity of garlic organosulfur compounds during dengue virus infection. Oxidative stress induced by lipid peroxidation has been shown to contribute to inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As oxidative stress is thought to be the mechanism through which dengue virus acts to trigger the pro-inflammatory immune response during infection, and garlic has previously been shown to suppress nitric oxide production [ 28 ], inhibit oxidative injury [ 29 ] and decrease reactive oxygen species (ROS) levels [ 32 ], we examined the anti-oxidant activity of garlic organosulfur compounds during dengue virus infection. Oxidative stress induced by lipid peroxidation has been shown to contribute to inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…The results of these studies suggest that blocking the oxidative stress response may reduce the pro-inflammatory response leading to severe symptoms in dengue virus infection. Garlic has been shown to suppress nitric oxide production through the inhibition of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells), downregulating expression of inducible nitric oxide synthase (iNOS) and blocking nuclear translocation of NF-κB [ 28 ]. Garlic has also been found to inhibit oxidative injury in liver through adenosine monophosphate (AMP)-activated protein kinase [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a recent research paper reported that the antiinflammatory activity of garlic OSCs help reduce TNF-α, IL-6, and iNOS [120], whether DADS can suppress inflammatory bowel disease and the molecular mechanisms haven't been investigated yet [116]. Many studies has been shown that DADS could suppress nitric oxide production through inhibiting the activation of NF-κB (nuclear factor kappa B), and attenuating expression of inducible nitric oxide synthase (iNOS) and blocking the nuclear translocation of NF-κB [121].…”
Section: The Inhibition Of Inflammation By Dadsmentioning
confidence: 98%
“…LPS activates NF-κB, a transcription factor that is involved in inflammatory response. Previous studies have indicated that aged red garlic extract and garlic oil derivatives such as DAS, DADS, and allyl methyl sulfide (AMS) could exert anti-inflammatory effects in LPS-stimulated RAW 264.7 macrophages through inhibition of iNOS expression, NO production, prostaglandin E 2 (PGE 2 ), and NF-κB (Liu et al, 2006;Shin et al, 2013;Lee et al, 2015;Ryu et al, 2015). ASC, an analogue of garlic compound, has been shown to exert an inhibitory effect on the growth of TM12 cells through modulating the expression of cell cycle regulatory proteins, inducing the loss of DNA integrity, and increasing the rate of apoptosis (Zhu et al, 2000a;Zhu et al, 2000b;Jiang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%